(untitled) (Research, Society and Development, 2026)
Major depressive disorder is associated with activation of immunoinflammatory responses and dysregulation of the hypothalamic–pituitary–adrenal (HPA) axis, directly influencing neurotransmission and brain homeostasis. This study aims to describe the mechanisms necessary for the diagnostic evaluation of major depression and neuroimmune dysfunction, explaining the influence of the immune system on central nervous system pathophysiology. This narrative literature review was conducted through searches in PubMed, Scielo, Cochrane, UpToDate, and Dynamed databases, including publications in Portuguese and English between 2005 and 2024. Evidence indicates that peripheral immune activation may impair blood–brain barrier integrity, promote neuroinflammation, and alter neurotransmitter availability such as serotonin, dopamine, and norepinephrine. Pro-inflammatory cytokines play a central role in neuronal dysfunction, while anti-inflammatory mediators may exert neuroprotective effects. It is concluded that the interaction between the nervous and immune systems significantly contributes to the pathophysiology of major depressive disorder.